Reading Aloud Activity in ESP Class in the Perspectives of Students - Titien Indrianti (Politeknik Negeri Padang, 2018)
Many studies have contradicted the reading aloud with silent reading instruction in EFL classroom. However, each viewpoint has its own arguments. Those in support of a silent reading claim that there exists psycho logical involvement in the mind of each reader and any written content. Through silent reading activity, students are trained to grasp the meaning of the text as int ended by the writer. On the other hand, the power of reading aloud cannot be seen as simplistic. Some believe that out loud reading instruction aid students to acquire new words and correct pronunciation, and comprehend language forms and mechanics, especially those with low English p roficiency. The students of Business Administration Department, State Polytechnic of Malang learn English as a foreign language in their ESP class. However, they still have insufficient English proficiency. In their English class, the reading aloud activity has been practiced as a method of instruction.On the basis of the above-mentioned background, this study intends to obtain the perspectives of students towards reading aloud activity in their ESP class. The problems of the study include (1) students’ viewpoint toward the benefit of reading aloud activity; (2) whether students feel any improvement in their English and aspects of the improvement; and (3) sorts of problems they encount er when dealing with reading aloud. The data are analysed qualitatively. The findings indicate that the students view a lot of benefits in reading aloud activity as it is building their self-confidence, recalling vocabulary, improving pronunciation, and managing pace and intonation in their reading.